Resolving the HIF paradox in pancreatic cancer. (1st October 2020) - Fuentes, Natividad R.; Phan, Jae; Huang, Yanqing; Lin, Daniel; Taniguchi, Cullen M.
Abstract: Pancreatic ductal adenocarcinoma (PDAC) is currently the third leading cause of cancer-related deaths and has a 5-year survival rate of less than 10%, far below the 70% national average for all cancers. This poor prognosis is driven by an extreme resistance to nearly all known cancer treatments, which has long been attributed to hypoxia driven interactions between tumor cells and the supporting stromal microenvironment. The cellular response to hypoxia is driven by the transcription factors known as the hypoxia inducible factors (HIFs), which have been hypothesized to play a role in the pathobiology of PDAC as well as a potential therapeutic target based on years of cell culture data. Attempts to validate the oncogenic role of HIF in PDAC through rigorous spontaneous tumor models have paradoxically shown that the HIFs may act as a tumor suppressor in epithelial cells. Here, we seek to resolve this paradox by discussing the roles of HIFs both in cancer cells and the supporting microenvironment and place them into context of current model systems that could be used to interrogate these interactions. We suggest that HIF may exert its oncogenic influences by modulating the form and function of the stroma rather than direct effects on cancer cells.